Integrasi Teori Perkembangan Kognitif Jeanpiaget dan Perkembangan Bahasa Vygotsky dalam Pembelajaran: Pemahaman dan Penerapan di Sekolah - Habsy, Bakhrudin All; Lestari, Pingkan Duwi; Maulidynan, Dinda Avrilia; Karim, Najwa Anisah (Lembaga Yasin AlSys, 2024)
Education has an important role in shaping children's development, especially in terms of cognition and language. In the cognitive development literature, Jean Piaget's theory and Lev Vygotsky's theory of language development have become two significant approaches in understanding how children learn, think, and communicate. This article combines these two theories and discusses their application in the context of learning in schools. Jean Piaget's theory of cognitive development emphasizes the stages of intellectual development that play a role in children's understanding of the world. In a learning context, this understanding can help teachers develop a curriculum that is appropriate to students' cognitive development stages. Meanwhile, Vygotsky's theory of language development highlights the role of social interaction and the environment in children's language development. The application of this theory includes a collaborative approach to learning that encourages more effective communication and language interaction in the classroom.